Provider Use of a Novel EHR display in the Pediatric Intensive Care Unit - Asan, Onur; Holden, Richard J.; Flynn, Kathryn E; Yang, Yushi; Azam, Laila; Scanlon, Matthew C (Applied Clinical Informatics, 2016)
The purpose of this study was to explore providers’ perspectives on the use of a novel technology, “Large Customizable Interactive Monitor” (LCIM), a novel application of the electronic health record system implemented in a Pediatric Intensive Care Unit.We employed a qualitative approach to collect and analyze data from pediatric intensive care physicians, pediatric nurse practitioners, and acute care specialists. Using semi-structured interviews, we collected data from January to April, 2015. The research team analyzed the transcripts using an iterative coding method to identify common themes.Study results highlight contextual data on providers’ use routines of the LCIM. Findings from thirty six interviews were classified into three groups: 1) providers’ familiarity with the LCIM; 2) providers’ use routines (i.e. when and how they use it); and 3) reasons why they use or do not use it.It is important to conduct baseline studies of the use of novel technologies. The importance of training and orientation affects the adoption and use patterns of this new technology. This study is notable for being the first to investigate a LCIM system, a next generation system implemented in the pediatric critical care setting. Our study revealed this next generation HIT might have great potential for family-centered rounds, team education during rounds, and family education/engagement in their child’s health in the patient room. This study also highlights the effect of training and orientation on the adoption patterns of new technology.Citation: Asan O, Holden RJ, Flynn KE, Yang Y, Azam L, Scanlon MC. Provider use of a novel EHR display in the pediatric intensive care unit: Large customizable interactive monitor (LCIM).
Keywords: Health information technology; pediatric intensive care units; workflow; clinical information systems/testing and evaluation